Effects of short-term nighttime carbohydrate restriction method on exercise performance and fat metabolism - Sakamoto, T.; Ueda, S.; Nakahara, H. (Nutrients, 2024)
Background: The sleep-low method has been proposed as a way to sleep in a low-glycogen state, increase the duration of low glycogen availability and sleep and temporarily restrict carbohydrates to improve exercise performance. However, long-term dietary restriction may induce mental stress in athletes. Therefore, if it can be shown that the effects of the sleep-low method can be achieved by restricting the carbohydrate intake at night (the nighttime carbohydrate restriction method), innovative methods could be developed to reduce weight in individuals with obesity and enhance athletes` performance with reduced stress and in a shorter duration when compared with those of previous studies. With this background, we conducted a study with the purpose of examining the intervention effects of a short-term intensive nighttime carbohydrate restriction method.